2006
DOI: 10.33776/amc.v32i141.2132
|View full text |Cite
|
Sign up to set email alerts
|

Relaciones de autoconcepto y la autoestima con sociabilidad, estabilidad emocional y responsabilidad en adolescentes de 14 a 17 años

Abstract: RESUMENEl estudio tiene tres objetivos: 1) analizar si existen diferencias en función del sexo en diversos parámetros de la personalidad durante la adolescencia; 2) estudiar las relaciones del autoconcepto y la autoestima con cooperación, habilidades sociales, sentimientos de felícidad, y otras dimensiones de personalidad; y 3) identificar variables predictoras de autoconcepto-autoestima. La muestra está constituida por 322 adolescentes de 14 a 17 años. El estudio utiliza una metodologfa descriptiva y correlac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
(53 reference statements)
3
14
0
18
Order By: Relevance
“…With respect to selfrelated aspects, there is evidence that adolescent girls tend to be more self-conscious (Rankin et al 2004) and ruminate more (Jose and Brown 2008) than their male counterparts. It also has been claimed that females may be better at identifying what they lack, in contrast to males, who may be better at identifying what they have (Garaigordobil and Durá 2006). Thus, low self-esteem, perfectionism and body dissatisfaction may be more detrimental for well-being in girls than in boys.…”
Section: Gender Differences In the Influence Of Risk And Protective Fmentioning
confidence: 87%
“…With respect to selfrelated aspects, there is evidence that adolescent girls tend to be more self-conscious (Rankin et al 2004) and ruminate more (Jose and Brown 2008) than their male counterparts. It also has been claimed that females may be better at identifying what they lack, in contrast to males, who may be better at identifying what they have (Garaigordobil and Durá 2006). Thus, low self-esteem, perfectionism and body dissatisfaction may be more detrimental for well-being in girls than in boys.…”
Section: Gender Differences In the Influence Of Risk And Protective Fmentioning
confidence: 87%
“…This study was performed using the hierarchical and multidimensional self-concept model (Shavelson et al 1976) in order to obtain a more sensitive, adjusted, and specific analysis of the measurements (Fuentes et al 2011). Previous studies have reported that adolescents with high self-concept have higher levels of psychosocial adjustment, such as greater satisfaction with life and less loneliness (Moreno et al 2009) and lower levels of depression and anxiety than adolescents with low self-concept (Garaigordobil and Durá 2006). In contrast, other authors have associated low self-concept with victimization (Kowalski and Limber 2013) and cybervictimization (Brewer and Kerslake 2015;Extremera et al 2018;Wachs et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…La experiencia en estrategias asertivas que estructuran las competencias sociales del adolescente supone un beneficio mutuo e individual para las partes implicadas en relaciones interpersonales (Elizondo, 2005). Las variables sociodemográficas en el constructo asertividad presentan oscilaciones en comparación con otras investigaciones (Garaigordobil y Durá, 2006;Onyeizugbo, 2003;Yoshioka, 2000), quizás debido a la utilización de diferentes instrumentos de evaluación en este campo, o por el posible efecto de deseabilidad social que puede producirse en los individuos a la hora de responder sobre su conducta asertiva.…”
Section: Discussionunclassified